Profiling the international academic ghost writers who are providing low-cost essays and assignments for the contract cheating industry. Issue 1 (19th October 2018) - Lancaster, Thomas
Abstract : Purpose: Students have direct access to academic ghost writers who are able to provide for their assessment needs without the student needing to do any of the work. These ghost writers are helping to fuel the international industry of contract cheating, raising ethical dilemmas, but not much is known about the writers, their business or how they operate. This paper aims to explore how the ghost writers market their services and operate, based on observable information. Design/methodology/approach: This paper reviews data from providers actively offering contract cheating services available to the public on Fiverr.com, a low-cost micro outsourcing site. The search term write essay is used to identify providers, finding 103 Gigs from 96 unique providers. Visible information, such as provider marketing, advertised services, pricing information and customer reviews, is analysed. Findings: The results demonstrate that bespoke essays are readily available to students at a low cost. The majority of providers operate from Kenya. Revenue calculations indicate a price point of US31.73 per 1, 000 words, below the cost of traditional essay mills, but show that these 96 providers have generated around US270, 000 of essay writing business between them. Originality/value: This study affords a look into a complex and established industry whose inner workings are normally kept private and for which little published information currently exists. The research adds to what is known about the extent, location and operation of the contract cheating industry.